The Value of Screening Parents for Their Risk of Developing Psychological Symptoms After PICU: A Feasibility Study Evaluating a Pediatric Intensive Care Follow-Up Clinic*. Issue 9 (November 2015) - Samuel, Victoria M.; Colville, Gillian A.; Goodwin, Sarah; Ryninks, Kirsty; Dean, Suzanne
Abstract : Objectives: This study aimed to assess whether prospectively screening parents for psychological vulnerability would enable beneficial targeting of a subsequent follow-up clinic. Design and Setting: Parents of children consecutively admitted to a PICU were assessed for risk of developing posttraumatic stress disorder at discharge using the Posttraumatic Adjustment Scale. Interventions: High-risk parents were then randomized to the intervention (follow-up clinic, 2 mo after discharge) or control condition. Measurements and Main Results: All parents completed Impact of Event Scale-Revised and Hospital Anxiety and Depression Scale at 6 months. Of the 209 parents of 145 children recruited to the study, 78 (37%) were identified, on the basis of their Posttraumatic Adjustment Scale score at baseline, as being at risk of developing posttraumatic stress disorder, and randomized to the control or intervention condition. Follow-up data were provided by 157 of 209 parents (75%). Logistic regression analyses controlling for parent gender and child length of stay showed that high-risk control parents ( n = 32) were significantly more likely to score above the clinical cutoff for all three psychological outcomes than parents deemed low risk at baseline ( n = 89) (posttraumatic stress: odds ratio = 3.39; 95% CI, 1.28–8.92; p = 0.014; anxiety: odds ratio = 6.34; 95% CI, 2.55–15.76; p < 0.001; depression: odds ratio = 4.13; 95% CI, 1.47–11.61; p = 0.007). Only 14 of 38 (37%) high-risk intervention parents attended the follow-up clinic appointment they were offered. At follow-up, there were no statistically significant differences between the intervention and control groups, but there were small effect sizes in favor of the intervention for anxiety scores (Cohen d = 0.209) and depression scores (Cohen d = 0.254) Conclusions: Screening parents for psychological vulnerability using measures such as the Posttraumatic Adjustment Scale may enable more efficient targeting of support. However, further research is needed on how best to provide effective follow-up intervention for families. Abstract : Supplemental Digital Content is available in the text.